Cervicogenic Dizziness Successfully Treated With Upper Cervical Medial Branch Nerve Radiofrequency Ablation: A Case Report - Zhu, Xiaoying (A A Pract, 2018)
Cervicogenic dizziness is a sensation of disequilibrium caused by abnormal afferent activity from the neck. Its diagnosis and treatment are challenging. In a case of cervicogenic dizziness, we performed diagnostic upper cervical medial branch nerve blocks with near complete symptomatic relief for around 20 hours. Radiofrequency ablation of these nerves resulted in near complete relief for 7 months. Subsequent repeat ablations provided the same relief lasting for 6–10 months. This case suggests that upper cervical medial branch block can serve as a diagnostic test for cervicogenic dizziness, and radiofrequency ablation of these nerves might be an effective treatment.